The complete chloroplast genome of Holboellia angustifolia (Ranales: Lardizabalaceae), a traditional herbal species. Issue 2 (3rd July 2019) - Wu, Xiaozhu; Li, Tongjian; Wen, Feng
Abstract: The complete chloroplast genome of Holboellia angustifolia was 157, 797 bp in length, displayed a typical quadripartite structure, composed of a LSC region of 86, 543 bp and a SSC region of 18, 972 bp, separated by a pair of IRs of 26, 141 bp each. The chloroplast genome contains 130 genes, consisting of 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Fifteen genes have one intron, and 3 genes contain two introns. The overall A/T content in the chloroplast genome of H. angustifolia was 61.31%. Phylogenetic analysis showed that H. angustifolia was closely related to Holboellia latifolia .